Program Pelatihan Pertanian Hidroponik P4S Excellent Farm - Saputra , Nurhasym (Najah: Journal of Research and Community Service, 2024)
The hydroponic agriculture training program organized by the Pusat Pelatihan Pertanian dan Pedesaan Swadaya (P4S) Excellent Farm aims to enhance farmers' capacity in implementing hydroponic cultivation techniques. This training covers various technical and managerial aspects of hydroponics, including the selection of appropriate hydroponic systems, preparation of growing media, plant nutrition, pest and disease control, and marketing of the harvest. The training methods used include lectures, discussions, demonstrations, and hands-on practice in the field. The results of this training program are expected to improve participants' knowledge and skills in hydroponics and encourage the efficient and sustainable application of hydroponic technology among farmers. Program evaluations show a significant increase in participants' understanding and abilities, as evidenced by the successful implementation of hydroponic techniques in their respective agricultural fields. Thus, this program is expected to contribute to the overall increase in productivity and well-being of farmers.